Peran Reksa Dana Syariah dalam Peningkatan Kegiatan Ekonomi di Indonesia - Cinta Rahmi; Moh Gufron; Raka Ahmad Rievai; Fauzan Firdaus; Alfridho Rayhansyah; Jibran Aufa Rajabi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Sharia mutual funds are becoming increasingly popular investment instruments in Indonesia because they comply with sharia principles. This research analyzes the role of mutual funds in increasing economic activity in Indonesia. The research method used is a literature study with secondary data analysis from sharia mutual fund performance reports. The research results show that the performance of sharia mutual funds is quite good with competitive returns compared to conventional mutual funds. However, there are several obstacles such as minimal socialization, limited choice of sharia investment instruments, and low public sharia financial literacy. With good management and stakeholder support, sharia mutual funds have the potential to encourage the growth of the sharia finance and investment industry in Indonesia.